2018
DOI: 10.2174/1874149501812010225
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Study of the Flows Caused by Dam Break around Downstream Obstacles

Abstract: Introduction: Studying dam break and the resultant flood routing along with identifying critical areas at the dam downstream are of great importance in safety management of the dam break issues. To reduce the risk of the dam break, an accurate estimation of the effective parameters on the energy dissipation due to the collapse of dams and the flood routing around the downstream natural and artificial obstacles is necessary. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Using three well-known turbulence models standard k   , k   , and k RNG   , the water level changes were compared with laboratory values at G1 and G5 points. By comparing the results obtained from different turbulence models, the RNG (Reynolds Normalized Groups) model was used, which is a highly recommended turbulence model for dam break simulation by numerous references [6,7,16,17].…”
Section: Model Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Using three well-known turbulence models standard k   , k   , and k RNG   , the water level changes were compared with laboratory values at G1 and G5 points. By comparing the results obtained from different turbulence models, the RNG (Reynolds Normalized Groups) model was used, which is a highly recommended turbulence model for dam break simulation by numerous references [6,7,16,17].…”
Section: Model Geometrymentioning
confidence: 99%
“…Azimi et al [16] and Issakhov et al [1] simulated the effect of different-shaped obstacles located downstream of a channel numerically using the Volume of Fluid (VOF) method. Feizi [17] studied dam break flow hydrodynamics in the presence of a cylindrical obstacle downstream of a channel. He used two different reservoir geometries, wide and long.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on analyzing flow stability through obstacles and flow speed [3][4][5][6][7]. These studies have identified ways to mitigate the risk of dam failure by accurately estimating the effective parameters concerning energy dissipation, dam collapse, and flooding direction around both natural and artificial obstacles downstream [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on analyzing flow stability through obstacles and flow speed [3][4][5][6][7]. These studies have identified ways to mitigate the risk of dam failure by accurately estimating the effective parameters concerning energy dissipation, dam collapse, and flooding direction around both natural and artificial obstacles downstream [3]. Additionally, Yaghoubi et al (2017) demonstrated that an area with negligible speed growth and increasing real concentration upstream around every obstacle becomes larger [5].…”
Section: Introductionmentioning
confidence: 99%